Microfinance – Once and Today - Reinhard H. Schmidt (Credit and Capital Markets – Kredit und Kapital, 2018)
– The paper sketches the history of the German savings and cooperative banks of the 19th century and that of modern microfinance in developing and transition countries of today and explores the parallels that exist between these two histories. One result is that the German savings and cooperative banks of the 19th century can rightly be regarded as precursors of modern microfinance. Another result, that also contains important practical and policy-relevant implications, is that the success of both the German popular banks of the 19th century and of a number of today"s microfinance institutions is due to a strategic shift undertaken quite early in their respective development: They have both abandoned their initial two-way specialization of offering only one type of financial services – either only loans or only deposit facilities – and of only addressing really poor people and very small businesses and instead adopted the role of genuine financial intermediaries, that offer loans and take clients" deposits, and broadened the spectrum of clients they aspire to reach, such that they have become truly inclusive financial institutions. Mikrofinanzierung früher und heute Der Beitrag skizziert die Entwicklung der deutschen Sparkassen und Genossenschaftsbanken im 19. Jahrhundert und die der vor etwa 50 Jahren entstandenen modernen Mikrofinanzinstitutionen und analysiert die Parallelen zwischen diesen beiden Gruppen "volksnaher" Finanzinstitutionen. Ein Ergebnis dieses Vergleichs ist, dass es durchaus gerechtfertigt ist, die frühen deutschen Sparkassen und Genossenschaftsbanken als Vorläufer der heutigen Mikrofinanzierung zu betrachten, wie es in der Literatur zu Microfinance gelegentlich angedeutet wird. Ein weiterer auch wirtschafts- und entwicklungspolitisch wichtiger Befund ist, dass beide Gruppen von Banken ihre beträchtlichen Erfolge einer radikalen strategischen Umorientierung verdanken, die sie recht früh in ihrer jeweiligen Entwicklung vollzogen haben: Beide haben ihre ursprüngliche doppelte Spezialisierung auf nur eine Art von Finanzdienstleistung – entweder nur auf die Kreditvergabe oder nur auf die Sammlung von Spareinlagen – und nur auf wirklich arme Menschen und nur auf sehr kleine Betriebe als Kunden aufgegeben und sich zu wirklichen Finanzintermediären entwickelt, die ihre Leistungen einem breiteren Kreis lokaler Kunden anbieten und somit als entwicklungsorientierte "inclusive banks" gelten können.
Keywords: G21; G16; G17; 330; Genossenschaftsbanken; deutsche Bankengeschichte; Sparkassen; Microfinance; inclusive banking